On the well-posedness of derichlet problems for the many-dimensional wave equation and lavrent’ev-bitsadze equation - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove the unique solvability of the Dirichlet problems for the many-dimensional wave equation and Lavrent’ev-Bitsadze equation.